PENGARUH KUALITAS PRODUK DAN KEUNGGULAN BERSAING TERHADAP KEPUTUSAN PEMBELIAN MELALUI LOYALITAS PELANGGAN - Apriyanti Apriyanti; Zelly Meylina Putri; Diyah Santi Hariyani (Valuasi : Jurnal Ilmiah Ilmu Manajemen dan Kewirausahaan, 2022)
The development of fashion in the clothing industry is currently growing rapidly. Many products offer quality, competitive prices in selling products. Likewise, what happened to Cardinal's product sales in Madiun City showed data on product sales in the past year, showing consumer interest in these products because they have good quality even though they are sold at quite high prices. While many other products offer lower prices, but do not have good product quality. This study aims to provide empirical evidence of the effect of product quality, competitive advantage on Cardinal product purchasing decisions through customer loyalty as a variable that intervenes Cardinal product consumers in Madiun City. This study uses an experimental quantitative approach. The sample size from 3 Mall outlets in Madiun City is 155 people. The sampling technique used was purposive sampling. The research instrument is a questionnaire. The data analysis technique uses path analysis. The results obtained from product quality affect purchasing decisions, but customer loyalty and competitive advantage have no effect on purchasing decisions for cardinal products in Madiun City